Challenges of glycoprotein analysis by microchip capillary gel electrophoresis. Issue 15 (14th July 2015) - Engel, Nicole; Weiss, Victor U.; Wenz, Christian; Rüfer, Andreas; Kratzmeier, Martin; Glück, Susanne; Marchetti‐Deschmann, Martina; Allmaier, Günter; Lapizco‐Encinas, B. H.; Hayes, M. A.
<x xml:space="preserve">Abstract</x> Glycosylations severely influence a protein's biological and physicochemical properties. Five exemplary proteins with varying glycan moieties were chosen to establish molecular weight (MW) determination (sizing), quantitation, and sensitivity of detection for microchip capillary gel electrophoresis (MCGE). Although sizing showed increasing deviations from literature values (SDS‐PAGE or MALDI‐MS) with a concomitant higher degree of analyte glycosylation, the reproducibility of MW determination and accuracy of quantitation with high sensitivity and reliability were demonstrated. Additionally, speed of analysis together with the low level of analyte consumption render MCGE attractive as an alternative to conventional SDS‐PAGE.